Trichogramma cordubensis (Hym.,Trichogrammatidae) walking behaviour at three different temperatures. - Garcia, Patrícia (1995)
Since wasps of the genus Trichogramma predominantly search for hosts by walking, it is important to study their walking behaviour to improve the success of biological control programs. Therefore this study is concerned with temperature effects on two parameters of the walking behaviour of T. cordubensis, walking speed and walking distance. The parasitoid walking distance differed significantly (p<0.05) between 15 and 25°C, and between 20 and 25°C. Although the parasitoid's walking speed at 25°C was higher than for the other two temperatures, no significant difference (p>0.05) was found among the three temperatures.